Social support and resilience as moderators of the relationship between COVID-19 pandemic-related trauma and posttraumatic growth in U.S. adults - Michael Berg; Linda Lin; Jenna Beebe; Hanna Ondrasek (Journal of Happiness and Health)
Previous research has established a positive association between COVID-19-related trauma and posttraumatic growth (PTG), but few studies have examined the factors that influence the strength of that relationship. The current study used an electronic survey to investigate the relationship between U.S. adults’ COVID-19-related trauma and PTG and the degree to which their perceived social support and psychological resilience served as moderators of that relationship. Data (n = 378) were gathered through a crowdsourcing platform in April, 2023. Analyses indicated a significant positive relationship between COVID-19-related trauma and PTG. In addition, both perceived social support and psychological resilience were supported as significant moderators of that relationship. Not only did higher levels of each variable predict a stronger relationship between trauma and growth, but they also had an interactive effect where having higher levels of both predicted the strongest relationship of all. This research establishes perceived social support and psychological resilience as key moderators of the relationship between COVID-19-related trauma and PTG. These results hold implications for how future research and therapeutic practice might benefit from focusing on perceived social support and psychological resilience as key factors in the psychological recovery from COVID-19.